The Students’ Listening Problems For Senior High School in Pematangsiantar - Rodesa Nauli Harianja; Nini Runggu Lumbantoruan; Anita Sinaga; Mertiviana Purba; Selviana Napitupulu (research, training and philanthropy institution Natural Aceh, 2022)
Abstract: This article describes the English listening problems faced by students in senior high school in Pematangsiantar. Specifically, it reveals (1) students' English listening skills, (2) problems they face in listening to English, and (3) how the teacher solves the problem. This article uses a qualitative descriptive method and is carried out in high school in Pematangsiantar, North Sumatra. the subject of this article through the purposive sampling technique. The data was obtained through a series of English listening tests using recordings with native and non-native speakers, observation, and interviews. The findings show (1) the problems they face in listening to English deal with speaking speed, limited vocabulary, level of concentration, and established language habits, and (3) To overcome this problem, the teacher applies the practice of the right way technique. by giving students several ways to practice listening to English. Thus, it can be concluded that the teacher's efforts are relevant to listening problems faced by students.